Mucin histochemistry of the columnar epithelium of the oesophagus (Barrett's oesophagus): a prospective biopsy study. Issue 6 (June 1984) - Peuchmaur, M; Potet, F; Goldfain, D
Abstract : Columnar epithelium-lined oesophagus (CELO) is an acquired disorder associated with a high incidence of cancer. CELO consists of three histological types of epithelium: gastric-fundic, junctional, and specialised columnar, the last resembling intestinal metaplasia of the stomach. In a previous study of CELO an incompletely differentiated variant of intestinal metaplasia secreting sulphomucins (type II B) was found. This was shown to be associated with well differentiated adenocarcinoma, as in the stomach. The purpose of this paper has been to define by histochemistry the mucin profile of CELO in 17 patients and to compare it with the mucin profile of the gastroesophageal junction in 27 patients without CELO. In CELO a specialised columnar epithelium was always found and type II B intestinal metaplasia (with sulphomucins) showed the highest incidence (53%). In normal subjects, this type of intestinal metaplasia was found in only three of 27 cases. Type II B intestinal metaplasia has often been considered as a precancerous lesion or as an equivalent of dysplasia; consequently, its high incidence in our study on CELO raises the question of whether this lesion should be considered a high risk condition for adenocarcinoma of the lower oesophagus.